Brazilian foreign policy in the Cardoso era: The search for autonomy through integration - Vigevani, Tullo [UNESP]; Oliveira, Marcelo Fernandes de [UNESP]; Thompson, Timothy (SAGE Publications, 2007)
The Fernando Henrique Cardoso administration attempted to replace a reactive foreign policy agenda dominated by a logic of autonomy through distance with a proactive international agenda guided by a logic of autonomy through integration. In adopting this agenda, the administration maintained that Brazil would be able to confront its problems and secure more control over its future if it actively contributed to elaborating the norms and guidelines of the administration of the global order. Because of structural weaknesses, however, this policy of integration, adherence, and participation was not adequately accompanied by positions entailing practical responsibilities - responsibilities that would have prepared both government and civil society for a higher profile in the post - cold-war era. In the end, the gains achieved during Cardoso's tenure failed to alter Brazil's international standing in any significant way. © 2007 Latin American Perspectives.
Keywords: Autonomy through integration; Brazilian foreign policy; Fernando Henrique Cardoso; Multilateralism; administration; autonomy; foreign policy; international relations; political integration; Brazil; South America